КОМПЕТЕНТНІСНИЙ ПІДХІД У ПЕДАГОГІЧНІЙ ТЕОРІЇ ТА ПРАКТИЦІ - Рожі, Інна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті охарактеризовано і розмежовано поняття «компетенція» та «компетентність», визначено, що компетенція характеризує освітній результат, а компетентність – сферу професійної діяльності особистості. Описано погляди відомих науковців і педагогів на основі поняття компетентності та дефініції компетентного підходу, їх роль у педагогічній теорії та практиці. Проаналізовано науково-педагогічну літературу і визначено, що поняття компетентність та компетентнісний підхід у вчених різниться через свій зміст, який визначається предметними й особистісними аспектами. В статье охарактеризовано и разграничено понятия «компетенция» и «компетентность». Определено, что компетенция характеризует образовательный результат, а компетентность – сферу профессиональной деятельности личности. Описаны взгляды известных ученых и педагогов на основные понятия компетентности и дефиниции компетентного подхода, их роль в педагогической теории и практике. Проанализировано научно-педагогическую литературу и определено, что компетентность и компетентностный подход отличаются через свой смысл, который определяется предметными и личностными качествами. The concepts of «competence» and «competency» have been described and delineated in the article. It has been defined that competence characterizes educational outcomes while competency deals with the sphere of professional activity of the individual. Views of well-known scholars and educators dealing with the notions of competency and competency-based approach definitions, their role in educational theory and practice have been described. Scientific and educational literature has been analyzed. It has been determined that the concept of competency and competency-based approach varies among scientists due to the content, determined by substantive and personal aspects. It has been established that the question of the essence of pedagogical concepts «competency» and «competence» is fundamental to the development of modern concept of competency-based approach in education. The analysis of their content, structure and relationships that makes it possible to improve the theory and methodology of the educational process and involves the formation of theoretical and practical readiness to perform professional functions has been done. Three-level hierarchy system of competencies has been determined.